60km格子全球大気モデルによる北極域の降水強度の将来変化 - 楠, 昌司; 水田, 亮; 保坂, 征宏; Shoji, KUSUNOKI; Ryo, MIZUTA; Masahiro, HOSAKA (2013)
Climate of the 20th and 21th century simulation was conducted with a 60km-mesh global atmospheric model (MRIAGCM3.2H) from year 1872 to 2099. For the historical simulation for 1872-2005, the model was forced with observed historical sea surface temperature (SST) and concentrations of green house gases such as CO2. For the future simulation for 2006-2099, the model was forced with SST changes projected by the average of Couple Model Intercomparison Project3 (CMIP3) multi-model ensemble. The A1B emission scenario is assumed. In order to evaluate uncertainty simulations, three member ensemble simulations with different atmospheric initial conditions were conducted. Measures of precipitation intensity such as Simple Daily precipitation Intensity Index (SDII) and maximum 5 day total precipitation (R5d) were calculated annually. Precipitation intensities (SDII, R5d) averaged over Arctic region (67.5-90N) increase monotonically in the 21st century. 第4回極域科学シンポジウム 個別セッション：[OM] 気水圏 11月14日（木） 統計数理研究所 ３階セミナー室１（D305） conference object